Plantation of fodder shrubs in arid and semi-arid zones of Iran - Nazari-Dashlibrown P. (Dynamics and sustainability of Mediterranean pastoral systems, 1999)
Iran's rangelands occur in the steppe, substeppe and xerophylous zones occupying 90 million hectares of the country. Topography is varied from 22m. below sea level up to 5670 m. elevation. Precipitation ranges from 25 mm. (central desert) to 1600 mm. (forest) per annum. Rangelands of the country have been in a poor condition for many years. Its current production provides only 20-25 per cent of the total feed requirements of existing herds and flocks which amount to 115 million sheep equivalents. Fodder shrub species such as: Atriplex spp, Artemisia herba-alba, and Erotia ceratoides are used to revegetate degraded rangelands.
9. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 1997/11/26-29, Badajoz (Spain)